The Role of Digital Technologies in Transforming Global Supply Chain Operations - Suganda, Fitrin Rawati; Judijanto, Loso (Yayasan Sinergi Kawula Muda, 2023)
This review explores how digital technologies—namely the Internet of Things (IoT), Artificial Intelligence (AI), and blockchain—are transforming supply chain management (SCM). Based on a structured review of recent peer-reviewed studies from databases like Scopus and Google Scholar, the findings show that these technologies enhance efficiency, visibility, and responsiveness. IoT enables real-time tracking and inventory accuracy, AI supports demand forecasting through predictive analytics, and blockchain ensures secure, transparent transactions. However, adoption is influenced by organizational culture, leadership, infrastructure, and regulations. Government policies play a key role in supporting digital transformation through incentives and standardization. The study highlights the need for multi-stakeholder collaboration and policy support to address challenges such as resistance to change, skill gaps, and infrastructure limitations. Future research should focus on longitudinal studies and the context of SMEs and developing regions. Modular integration, collaborative ecosystems, and sustainability-driven innovation are essential for building resilient, adaptive supply chains in the digital era.